Deployment of new dynamic cryptography buffer for SCADA security enhancement - Aamir, Shahzad; Musa, Shahrulniza; M., Irfan; Shah, Asadullah (Asian Network for Scientific Information, 2014)
The current study is based on novel solution which deploy the security mechanism, more advance cryptography solution within distributed Network Protocol (DNP3) stack as a part of critical system (or SCADA) system). The "Dynamic Cryptography Buffer (DCB)" has been implemented that contains 56 bytes from total size of " Application Protocol Data Unit (APDU) bytes" as a part of application layer of DNP3 protocol. The DCB contains several fields/sub-fields which have been used during implementation of cryptography algorithm and other information ( or detail) related with protocol security. During implementation with DNP3 protocol, the bytes are dynamically stored after processing ( security deployment) within DCB, without affecting the total size of DNP3 protocol stack. This novel study gives new directions for SCADA or its protocols security deployment and enhancement.